Temperature-Dependent Circularly Polarized Luminescence Measurement Using KBr Pellet Method - Kondo, Yoshiro; Suzuki, Satoko; Watanabe, Masayuki; Kaneta, Akio; Albertini, Paolo; Nagamori, Koushi (Frontiers in Chemistry, 2020)
Circularly polarized luminescence (CPL) spectroscopy measures the difference in luminescence intensity between left- and right-circularly polarized light, and is often used to analyze the structure of chiral molecules in their excited state. Recently, it has found an increasing range of applications in the analysis of molecules that emit circularly polarized light and can be employed in 3D displays. Thus, the number of articles focusing on CPL spectroscopy has increased dramatically. However, since the luminescence dissymmetry factor (glum) for organic compounds is generally less than |0.01|, CPL spectrometers must offer high sensitivity and produce spectra that are artifact-free for achiral molecules. Until now, the principal targets of CPL measurements have been solution samples. However, for practical device applications, it is also necessary to be able to measure the CPL spectra of solid-state samples. In addition, since electronic devices often operate at high temperatures, it is important to evaluate the thermal dependence of the CPL characteristics. Therefore, it is necessary to further develop CPL spectrometers and measurement techniques. To this end, we describe recent advances in CPL spectroscopy and its applications to solid-state samples at high temperatures.